Relationship Between Management Accounting Attributes and User Satisfaction - Fabio Frezatti; Andson Braga de Aguiar; Amaury Jose Rezende (Journal of Accounting, Business and Management (JABM), 2006)
This article analyzes the relationship between the attributes of a management-accounting information system (MAIS) and satisfaction among the users of a given system. The qualitative characteristics of accounting information, and the particular attributes of the MAIS that is used, contribute to the user satisfaction but a linkage with use/usefulness and user value of management-accounting information must be considered in terms of decision-making. In the present study, the definitions of MAIS attributes are derived from the constructo provided by Chenhall and Morris (1986) and consolidated by Moores and Yuen (2001). These are applied to data collected in a field study of medium-sized and large Brazilian companies. Data analysis includes multivariate analysis by means of the cluster method. Results indicate that the satisfaction of users of a MAIS increases if the attributes of the system allow users to obtain useful information. Future research can examine which attributes of an MAIS make a greater contribution to the satisfaction of users of accounting information.